2023
DOI: 10.1172/jci.insight.162409
|View full text |Cite
|
Sign up to set email alerts
|

Association of self-identified race and genetic ancestry with the immunogenomic landscape of primary prostate cancer

Abstract: The genomic and immune landscapes of prostate cancer differ by self-identified race. However, few studies have examined the genome-wide copy number landscape and immune content of matched cohorts with genetic ancestry data and clinical outcomes. Here, we assessed prostate cancer somatic copy number alterations (sCNA) and tumor immune content of a grade-matched, surgically treated cohort of 145 self-identified Black (BL) and 145 self-identified White (WH) patients with genetic ancestry estimation. A generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
(136 reference statements)
0
6
0
Order By: Relevance
“… 16–20 ). We recently published Infinium EPIC methylation profiling data on a subset of this cohort ( 21 ) as described below, and samples were also arrayed on tissue microarray (TMA) for immunostaining studies as described previously ( 16 ). The second cohort was also from JHU but included in the Prostate Cancer Biorepository Network (PCBN cohort) and comprised 57 WH and 58 BL men with radical prostatectomies occurring between 2014 and 2016, also matched for Grade Group and selected to overrepresent higher Grade Groups, and arrayed on a TMA ( 22–26 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 16–20 ). We recently published Infinium EPIC methylation profiling data on a subset of this cohort ( 21 ) as described below, and samples were also arrayed on tissue microarray (TMA) for immunostaining studies as described previously ( 16 ). The second cohort was also from JHU but included in the Prostate Cancer Biorepository Network (PCBN cohort) and comprised 57 WH and 58 BL men with radical prostatectomies occurring between 2014 and 2016, also matched for Grade Group and selected to overrepresent higher Grade Groups, and arrayed on a TMA ( 22–26 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a subset of 111 of these patients had RNA microarray profiling which has been previously published on the Decipher platform ( 19 ). DNA samples isolated from formalin-fixed paraffin-embedded tumors were analyzed using the Infinium EPIC methylation array platform as described recently, and compared with 30 benign prostate tissues from a subset of the WH and BL men ( 21 ). The second cohort was the previously published The Cancer Genome Atlas (TCGA) prostatic adenocarcinoma cohort, where Infinium 450K methylation array profiling data were available from tumors from 502 men, with matched benign samples from 50 men ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is necessary to fully understand the implications of these observed differences and their potential contribution to racial disparities in prostate cancer. Some of these data have recently been published 9 …”
Section: Impact Of Molecular and Genomic Factors On Prostate Cancer D...mentioning
confidence: 99%